An Existentialist Interpretation of the Song ‘Tanpa Aku’ by Panji Sakti - Khasanah, Faridhotul; Rofhani, Rofhani (Journal of Islamic Thought and Philosophy, 2025)
Songs serve not only as aesthetic works, but also as a medium for existential reflection that mirrors the inner struggles of humans in their search for meaning in life. This article analyzes the song “Tanpa Aku” (Without Me) by Panji Sakti through the approach of Soren Kierkegaard's existentialism, with the aim of understanding the representation of human existence in song lyrics. This study analyzes the song's lyrics using a semiotic approach. The results show that the lyrics of “Tanpa Aku” describe the existential journey of humans, which begins with an aesthetic experience of alienation and loss of meaning, then develops into ethical awareness through moral reflection, and finally reaches a religious stage marked by surrender to God. Thus, “Tanpa Aku” is not only a work of music with aesthetic value, but also a philosophical text that brings together music and philosophy.